Specificity of late-night salivary cortisol measured by automated electrochemiluminescence immunoassay for Cushing’s disease in an Obese population - Jens Aberle and C. Schulze zur Wiesch and J. Flitsch and Jochen Veigel and G. Schön and Roman Jung and F. Reining and Anne Lautenbach and R. Rotermund and Nina Riedel (Journal of endocrinological investigation : JEI, 2018)
Purpose